Diseño y comercialización de artículos deportivos skateboards en la ciudad de Machala. - San Martin Cuenca, Jimmy Gabriel (2018)
The research project developed responds to the demand presented by the population of Machala to acquire a quality skateboard product. With the application of a specialized manufacturing process for the skateboarding area, the study was carried out to determine the most convenient production process in order to reduce costs and save resources in the transformation of the product. When there is no bidder of a local product of this type, the study was carried out that led to the search of suppliers of raw material and semi-finished products abroad, due to the ignorance of factories in Ecuador that make this semi-finished skateboard product. It was in this way that the issue of importation was applied, also carrying out the various procedures that this purchase system has, to be later manufactured and processed. The product is mainly aimed at a potential youth market, therefore the main objective is the implementation of a micro-company dedicated to the design and commercialization of skateboards with high quality standards in the city of Machala, El Oro Province, covering their demand and achieving the positioning of the same, through a quantitative exploratory market study with real information data that allowed to establish according to the survey, product demand and the potential market in the city of Machala. The project established a series of processes that determine the problem presented by the current market of this product, from its price in the market to the details by which the customer prefers one brand of another, thus showing real information about consumers. , practitioners of this sport, tastes and preferences, prices and more data that normalize the production activities, in order to develop a quality product for the client. The number of monthly and annual production units was established in the same way according to the installed capacity in the factory, and according to the survey data, which served to generate the calculation of the demand of the sample taken from the population of the city of Machala. province of El Oro. According to the data taken, it was established that a small part of the population is dedicated to this sport regardless of the cost, which is why this project was developed by observing a price problem of this product, which is significantly expensive and which saw a business opportunity in the absence of a producer of a local skateboard brand. The present project looks to the future in order to be able to take these products not only to the market of the city of Machala but hoping to expand its sales throughout the province of El Oro and Ecuador. The concepts and definitions established in the body of the project served as the basis to sustain and defend the generated data, finally providing real information about environments, competitors and mainly economic factors whose results according to the VAN and TIR determined the profitability and viability of the project.